Determinants of Return on Assets and Implications on Stock Price Changes Level - Riyani, Yani; Mardiah, Kartawati; Suherma, Linda (International Journal of Economics and Financial Issues, 2019)
This study aims to determine the effect of loan to deposit ratio and non-performing loans on Return On Assets and Implications for Stock Price Rate of Change using SPSS 16.0 statistical software. In this study, there are 4 variables: Loan to Deposit Ratio and non-performing loans as independent variables (X1 and X2) and Return on Assets and Stock Price Rate of Change as a dependent variable (Y) and (Z). The research method used is a causal associative method that aims to determine the relationship between two or more variables. Effect of Loan to Deposit Ratio, Non Performing Loan to Return On Assets. Based on the results of SPSS processing, it can be concluded that the influence of Loan To Deposit Ratio and non-performing loans to levels not significantly change in the stock price. While the level of stock price changes is influenced by the Loan to Deposit Ratio and non-performing loans amounted to 2.10% while the remaining 97.90% is influenced by other factors. Keywords: Loan to Deposit Ratio, Non Performing Loan, Return on Assets, Stock Price JEL Classifications: G32, G38, G28 DOI: https://doi.org/10.32479/ijefi.7616